Pengaruh Motivasi dan Kompensasi Terhadap Kinera Karyawan pada Desa Wisata Pa‟tengko Kabupaten Tana Toraja - Nurhasni Batara; Althon K. Pongtuluran (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The purpose of this research is to determine the effect of motivation ang compensation on employee performance in the Pa‟tengko Tourism Village. The type of research used is quantitative research. The population in this research is all 32 employees in the Pa‟tengko Tourism Village and the sample used is saturated sampling. That is,the entire population was sampled. The methods used in this research include Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Test, t Test (Partial), f Test (Simultaneous), Correlation Test and Determination Test (R2). The data was processed using SPSS software version 26. The results of this research show that (1) motivation has a positive and significant effect on employee performance in Pa‟tengko Tourism Village. (2) compensation has a positive and significant effect on employee performance in Pa‟tengko Tourism Village. (3) motivation and compensation simultaneously have a positive and significant effect on employee performance in the Pa‟tengko Tourism Village.